Case Report: A case report and literature review of shwachman-diamond syndrome concurrent with klinefelter syndrome - Chang, Chenyang; Chen, Hao; Zhang, Hao; Chen, Jingshan; Wan, Qinxin; Zhu, Huifang; Luo, Kaiyuan; Rao, Xingyu (Frontiers in Pediatrics, 2025)
Shwachman-Diamond syndrome (SDS) is a rare genetic disorder characterized by pancreatic insufficiency, metaphyseal chondrodysplasia, and bone marrow failure. These clinical features collectively contribute to the multisystemic nature of SDS, affecting multiple organ systems. In contrast, Klinefelter syndrome is defined by the presence of an additional X chromosome. Its clinical presentation primarily includes an abnormal testicular microenvironment, impaired spermatogenesis, decreased testosterone levels, and elevated gonadotropin levels. We identified a pediatric patient presenting with SDS concomitantly diagnosed with Klinefelter syndrome, characterized by a splice-site in the Shwachman-Bodian-Diamond Syndrome (SBDS) gene and a mosaic karyotype of 47,XXY/46,XY(Klinefelter syndrome). A 6-month-old infant was admitted to the hospital with elevated liver enzymes and neutropenia persisting for more than two weeks. Additional investigations revealed granulocytopenia, increased liver enzyme levels, and reduced fecal elastase, raising strong suspicion of SDS. Whole exome sequencing (WES) was conducted on the proband and both parents, revealing a homozygous variant in the SBDS gene (c.258+2T>C) located on chromosome 7 in the proband. Concurrently, the karyotype analysis demonstrated a mosaic pattern consistent with 47,XXY/46,XY(Klinefelter syndrome). The objective of this study is to improve the understanding of SDS and Klinefelter syndrome through a detailed analysis of their clinical manifestations and genetic profiles. This work aims to establish a solid molecular basis for etiological diagnosis, genetic counseling, and prenatal diagnosis of these syndromes.